Pemberdayaan Kader Posyandu Dalam Pencegahan Stunting Di Desa Tanjung Kamal Kecamatan Mangaran Kabupaten Situbondo - Nanang Tri Haryadi; Rahma Mar’atus Sholikhah; M. Hilman Nur Farodis; Reza Oktavianus; Intan Karina Mutiara; Sandra Nurmeiswara Putri; Miftakhul Jannah; Dhevischa Alamanda Iriyanto; Dian Siska Safitri; Aziz Surahman; Titin Agustina (Universitas Pahlawan Tuanku Tambusai, 2023)
According to the BAPPEDA of Situbondo Regency, in 2022 there were 88 stunting cases in Tanjung Kamal Village. Tanjung Kamal Village is one of the villages that are of concern to the Situbondo government in preventing stunting in 2023. The problem with preventing stunting in this village is that Posyandu volunteers' knowledge of stunting is still limited. Posyandu volunteers have an important role in stunting prevention, so it is necessary to increase their knowledge of stunting prevention. This community service activity aims to provide education related to the importance of stunting prevention for Posyandu cadres in Kamal Village. Service activities include counseling about stunting, the practice of making complementary food menus for breast milk (MP-ASI) according to village potential, and making stunting prevention guidebooks. The result of this service is an increase in the knowledge and skills of Posyandu cadres in Kamal village regarding stunting and the creation of MP-ASI so that it can help educate Posyandu members.